Anak dalam Patologi Kehidupan Seksual Keluarga Transmigran - Nur Rahmah; Subhan; Esti Ningsih; Yusannang (HMPS PIAUD FTIK IAIN Jember, 2020)
Transmigrant families must deal with the territorial transitional problems of new territories. In new areas, families are not easy to start fulfilling epective food because of the unprepared land conditions. Many families lack the material to build a